Co-creating and Developing Health Management Theory and Practice: a global opportunity? - David Briggs (ACHSM, 2018)
In recent years much has been made of the need to effectively translate knowledge developed through research into health systems practice. [1] Literature suggests that the acceptance of research findings would be more likely if the research were achieved and disseminated into practice where it occurs in a more collaborative alignment of researchers and practitioners.....